Inaugural issue perspectives on Information and Learning Sciences as an integral scholarly Nexus. Issue 1 (14th January 2019) - Reynolds, Rebecca; Chu, Sam; Ahn, June; Buckingham Shum, Simon; Hansen, Preben; Haythornthwaite, Caroline; Huang, Hong; Meyers, Eric M.; Rieh, Soo Young
Abstract : Purpose: The new journal, Information and Learning Sciences, aims to advance the understanding of human inquiry, learning and knowledge building in human design and uses of information systems, e-learning systems and socio-technical system contexts. Design/methodology/approach: Under the new editorial team, advisory board, and reviewer community, the authors aim to develop and provide an established and rigorous space for scholarly development that explores phenomena at the intersections of these two fields of inquiry. The editorial advisory board brings together over 70 leading international scholars who are evenly divided between and across these two disciplines. Findings: To chart the course for the journal's scope and mission and set a standard for quality, the editorial team decided to launch with an inaugural issue of eight articles comprising mainly of theoretical syntheses and editorial essays, alongside three works that report empirical study research findings as exemplars. Authors were chosen by the editorial team based on their known thought leadership at this intersection, and the articles underwent a single-blind review process with a period of revisions. All articles and issues moving forward will be double-blind peer reviewed under both fields' expected norms and standards of rigorous editorial excellence. The authors invite all interested experts and experts-in-development in our two disciplines, to submit work and volunteer as reviewers in these pursuits. The authors present a brief summary narrative discussing a selection of four recent areas of interdisciplinary research out of which the journal has emerged. The authors then describe each of the special issue articles contributed by our generous invited authors. Originality/value: The authors enthusiastically and warmly invite continued engagement along these lines in the journal's pages, and also welcome related, and wholly contrary points of view, and points of departure that may build upon or debate some of the themes we raise in this introduction and inaugural issue.